1999
DOI: 10.1002/(sici)1521-3765(19990104)5:1<208::aid-chem208>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Type A Photocatalysis: Role of Substrate Adsorption and the Nature of Photoreactive Surface Sites in Zinc Sulfide Catalyzed C-C Coupling Reactions

Abstract: The mechanism of the photodehydrodimerization of 2,5-dihydrofuran (2,5-DHF) by suspended zinc sulfide powders was investigated through emission, inhibition, adsorption, and quantum yield studies. Zinc and cadmium ions influenced the emission intensity only marginally but strongly inhibited the reaction, so the photoreactive surface sites were not identical with the emitting states, which had lifetimes in the 0.1 ± 24 ns range. Adsorption isotherms for these metal ions and 2,5-DHF in aqueous solution indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 17 publications
(28 reference statements)
1
63
1
2
Order By: Relevance
“…[22][23][24] The photocatalytic carboxylation of organic compounds under mild conditions extends this list. [28] A different mechanism of CO 2 photocoupling was reported by Yanagida and co-workers, who suggested that cadmium sulfide would promote the intermolecular addition of CO 2 to a C=O bond. This mechanism is characteristic of type B photocatalysis, which involves the coupling of two radicals, in contrast to type A photocatalysis, which is characterised by the formation of various reduction and oxidation products.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[22][23][24] The photocatalytic carboxylation of organic compounds under mild conditions extends this list. [28] A different mechanism of CO 2 photocoupling was reported by Yanagida and co-workers, who suggested that cadmium sulfide would promote the intermolecular addition of CO 2 to a C=O bond. This mechanism is characteristic of type B photocatalysis, which involves the coupling of two radicals, in contrast to type A photocatalysis, which is characterised by the formation of various reduction and oxidation products.…”
Section: Introductionmentioning
confidence: 94%
“…[28] In contrast, zinc sulfide, which is a wide band gap (3.6 eV) semiconductor, offers particularly strong reduction potentials, as low as À1.8 to À2.0 V versus SHE, and its activity in photocatalytic water splitting and carbon dioxide reduction has been demonstrated. The commonly used TiO 2 photocatalyst does not enable this process because the bottom of its conduction band is located at about À0.3 to 0.6 V versus SHE, depending on the sample and pH conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Since the radical is stabilized by its two resonance structures, its lifetime is sufficient to enable bimolecular reactions. This reaction proceeds through the formation of allylic radicals (hydrogen abstraction from 2,3-DHF), identical to that formed in the reaction of 2,5-DHF oxidation by valence band holes generated upon irradiation of ZnS and CdS.…”
Section: Discussionmentioning
confidence: 99%
“…Dies gilt vor allem auch für kolloidale Halbleiter, die sich zwar auf Grund ihrer pseudohomogenen Natur konventionell untersuchen lassen, aber als Photokatalysatoren für Synthesen zu labil waren [16]. Wie schon erwähnt, verhindert in den meisten Fällen die Photokorrosion des Halbleiters einen Einsatz in der chemischen Synthese.…”
Section: Typische Reaktionenunclassified
“…Da die Reaktionsgeschwindigkeit mit dem Quadrat der Konzentration an adsorbiertem 2,5-DHF (n eq ) ansteigt, kann man ferner auf eine C-C-Kupplung zwischen adsorbierten Radikalen schließen, weil die Konzentration der Dihydrofurylradikale direkt proportional zu n eq sein sollte [16]. Dies entspricht dem klassischen Fall der heterogenen Dimerisierung nach einem Langmuir-Hinshelwood-Mechanismus.…”
Section: S O L a R E C H E M I E | Halbleiter-photokatalyseunclassified